Implementasi Program Wirausaha Merdeka melalui Workshop Pembuatan Bouquet Snack - Revita Yanuarsari; Dianti Yunia Sari; Sandra Noor Utami (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
The era of the industrial revolution 4.0 and society 5.0 brought many challenges for students, one of which was that students were required to have an independent, creative and innovative character so that after graduation they would not only act as job seekers but could create jobs. To form the character of students who are independent, creative and innovative, practical and practical workshops are needed so that the results of the workshops can be directly applied in the real world. The bouquet snack making workshop is an interesting and practical workshop to learn in a short time. In line with one of the independent learning campus independent programs (MBKM), namely the independent entrepreneur program, the workshop for making bouquet snacks can provide skills for students so that after graduation they have additional skills and expertise that can be used to create jobs because making bouquet snacks is relatively easy.